The 4th Regional Dental Meeting and Exhibition Medan, Indonesia 18-20 November 2009 - Sam'an Malik, Masudi (Pusat Pengajian Sains Pergigian, 2009)
Removing of smear layer is an essential step for endodontic success. Smear layer is formed during and after canal preparation. The aim of study was to compare the cleaning efficiency of smear layer using syringe irrigation method and using polymer-based rotary file for fluid agitation on prepared root canal surfaces under scanning electron microscope (SEM) study. A total of 32 extracted mandibular second premolar teeth were used. All teeth were randomly divided into two groups, Group I (01) and Group 2 (02). For irrigation, all teeth in 01 were irrigated alternate use of 5% NaOCI and 17% EDTA by irrigation syringe with 27-gauge needle. For 02 irrigation procedure was the same as 01, but for final irrigation, canal was filled with 5% NaOCl and polymer-based rotary file with the rotation speed of 600-900 rpm at 30s was used for agitation of fluid. All teeth in both groups were split longitudinally and prepared for SEM evaluation. The presence of smear layer was evaluated from photomicrographs at x!OOO magnification taken in the apical, middle and coronal third of the canal surfaces. A five category scoring system was used. Blind evaluation was performed by three trained observers for scoring. Statistical analysis was carried out using Mann-Whitney test. The result showed that smear layer score was statistically significantly lower after using polymer-based rotary file than after syringe irrigation. In conclusion using polymer-based rotary file is more efficient than syringe irrigation for smear layer removing especially on the apical third of the prepared canals.